2017
DOI: 10.1002/ddr.21384
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Protective Effect of Phenolic‐Enriched Ethylacetate Fraction of Ocimum gratissimum (Linn.) Leaf against Acute Inflammation and Oxidative Stress in Rats

Abstract: Preclinical Research Ocimum gratissimum L. leaves have attracted considerable attention from researchers because of their medicinal value that include anti-inflammatory, analgesic, antimicrobial, and antioxidant activities. In the present study, the toxicity and the protective effect of phenolic extract of O. gratissimum leaf (EAFOg) against acute inflammation and oxidative stress in rats was assessed. EAFOg, enriched in phenols had no cytotoxic effect against CHO-k1 cells, and no lethality against brine shrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
2
10
0
2
Order By: Relevance
“…The cells' protection against H 2 O 2 oxidative stress was also in agreement with a recent in vivo study showing that an Ocimum gratissimum leaf phenolic extract protected rats against acute inflammation and oxidative stress [18]. Likewise, an aqueous Ocimum gratissimum extract revealed antioxidant and cytoprotective activities in the presence of hydrogen peroxide-induced toxicity in human HepG2 cells [34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The cells' protection against H 2 O 2 oxidative stress was also in agreement with a recent in vivo study showing that an Ocimum gratissimum leaf phenolic extract protected rats against acute inflammation and oxidative stress [18]. Likewise, an aqueous Ocimum gratissimum extract revealed antioxidant and cytoprotective activities in the presence of hydrogen peroxide-induced toxicity in human HepG2 cells [34].…”
Section: Discussionsupporting
confidence: 89%
“…ex Tedlie (Cecropiaceae family). In vivo studies demonstrated that Oc leaf extracts possess both in vitro and in vivo hypoglycemic properties [12][13][14][15][16][17][18][19]. Recently, Musanga cecropioides (Mu) leaves or stem bark extracts have shown an antidiabetic potential [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been developed to evaluate the safety, efficacy, and toxicity of nutraceutical products and their active ingredients. Bioactive ingredients present in nutraceuticals have exhibited diverse pharmacological properties such as antioxidant, sedative, hypnotic, anti-inflammatory, immuno-modulatory and adaptogenic attributes [ 219 , 220 , 221 , 222 , 223 ]. Subsequently, these products were applied and their efficiency appraised using in vitro, in vivo, in silico, high-throughput in vitro, and omics technology-reliant assays [ 224 ].…”
Section: Nutraceuticals’ Safety On Consumersmentioning
confidence: 99%
“…However, its phenolics constituents such as flavonoids have been reported to possess great free radical scavenging property and therefore responsible for most of its antioxidant effects [41]. These phenolics have also been reported to be highest in the ethyl acetate fraction of the crude methanolic extract [42]. They are principally important because, even at low concentrations, they retained their roles at scavenging free radicals that may accelerate oxidative cellular damage via membrane or tissue protein injury, degradation of vital cellular enzymes, carbohydrate metabolism imbalance and modification of the cells’ genetic material [43].…”
Section: Discussionmentioning
confidence: 99%